The Influence of Communication and Service Quality on Community Satisfaction at the Kebonrejo Urban Village Office, Salaman District, Magelang Regency: Pengaruh Komunikasi dan Kualitas Pelayanan terhadap Kepuasan Masyarakat di Kantor Kelurahan Kebonrejo, Kecamatan Salaman, Kabupaten Magelang - Ismun Ismun; Sugiharti Sugiharti (Lembaga Riset dan Inovasi Masyarakat Madani, 2026)
Public service at the urban village level plays an important role in shaping community satisfaction with local government services. This study aims to analyze the influence of communication and service quality on community satisfaction at the Kebonrejo Urban Village Office, Salaman District, Magelang Regency. This research used a quantitative approach with multiple linear regression analysis. Data were collected from 150 respondents using purposive sampling through questionnaires distributed from January to March 2026. The results show that communication has a positive and significant effect on community satisfaction (t = 4.738, p < 0.001), service quality has a positive and significant effect on community satisfaction (t = 8.308, p < 0.001), and communication and service quality simultaneously have a significant effect on community satisfaction (F = 45.321, p < 0.001). The adjusted R square value of 0.373 indicates that communication and service quality explain 37.3% of the variation in community satisfaction. Based on the standardized beta value, service quality is the dominant factor influencing community satisfaction. These findings imply that improving service responsiveness, reliability, and communication clarity can support better public service delivery at the urban village office level.